2008
DOI: 10.1016/j.polymer.2008.07.035
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of vibrational intensity with fluorescence lifetimes in π conjugated polymers

Abstract: a b s t r a c tA series of novel pi (p) conjugated polymers, originating from the archetypical Polyphenylene vinylene, in which the phenyl units are successively replaced by the larger naphthyl and anthryl acene units, were previously found to have a well-defined relationship between their relative fluorescence yields and their vibrational characteristics, as determined by Raman spectroscopy. In this study the Strickler-Berg equation is used to probe the influence of continual substitution of higher order acen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Well-defined relationships relating the variation in conjugation across the π back-bone to vibrational coherence have served to establish empirical relationships describing the variation of the fluorescence yield with Stokes shift, integrated Raman intensity and electronic band-gap [19,20,21,22].…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…Well-defined relationships relating the variation in conjugation across the π back-bone to vibrational coherence have served to establish empirical relationships describing the variation of the fluorescence yield with Stokes shift, integrated Raman intensity and electronic band-gap [19,20,21,22].…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%
“…When the excited electrons relax mainly through radiative decay processes, increased QYs will be observed. If the contribution of non‐radiative processes is significant, the opposite will be expected . Using the relationship between the fluorescence lifetime ( τ F ) and QY ( Φ F ), k nr = (1 − Φ F )/ τ F , the radiative and non‐radiative decay rates of PPEs and PPBs were obtained before and after complexation (Table , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the systematic variation of the vibrational coupling along the backbone results in a systematic decrease in the non-radiative decay rates and thus an optimisation of the radiative yield. The systematic variation of the electron density of the vinylene bond of the polymer series by the introduction of naphthalene and anthracene moieties into the backbone [9,10,11] suggests that the photo-active stability can be similarly improved. This report presents a systematic study of the relative stabilities of polymers 1-6 ( Figure 1 The mechanisms and results of such degradation in conjugated polymers have been studied and presented at length in the literature [12].…”
Section: Introductionmentioning
confidence: 99%